The hunchback of Notre Dame - Stewart, Diana; Shaw, Charles, 1941-2005; Hugo, Victor, 1802-1885. (Milwaukee : Raintree, 1981)
Retells in simple language the tale of the hunchbacked bellringer of medieval Notre Dame, Quasimodo, whose love for the gypsy dancer, Esmeralda, had tragic consequences.
Keywords: Notre-Dame de Paris (Cathedral) -- Fiction; People with disabilities -- Fiction; France -- History -- Medieval period, 987-1515 -- Juvenile fiction; France -- History -- Medieval period, 987-1515 -- Fiction; Paris (France) -- Fiction